2009
DOI: 10.1016/j.scitotenv.2008.11.061
|View full text |Cite|
|
Sign up to set email alerts
|

Structural and physiological responses to ozone in Manna ash (Fraxinus ornus L.) leaves of seedlings and mature trees under controlled and ambient conditions

Abstract: Leaf-level microscopical symptom structure and physiological responses were investigated in seedlings experimentally exposed to ozone (O3) in indoor chambers (150 ppb, 8 h d(-1)/7 weeks), and field trees of Manna ash (Fraxinus ornus) exposed to ambient O3 (max 93 ppb/one growing season). Ozone-induced leaf injury, including leaf reddening and stippling, was observed in both seedlings and mature trees, but the morphology of injury in the stipples differed, being hypersensitive-like (HR-like) in the chamber seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 50 publications
5
41
0
1
Order By: Relevance
“…OB triggers programmed death, leading to a cell collapse as observed in stippling areas in AA and PO. As shown in the present study, palisade parenchyma is usually the most affected tissue by O 3 (Günthardt-Goerg and Vollenweider, 2007;Paoletti et al, 2009). Our observations suggest that reactive oxygen species (ROS) degrades the pectins of the middle lamella inducing a separation of the mesophyll cells, and increasing intercellular spaces.…”
Section: Discussionsupporting
confidence: 77%
“…OB triggers programmed death, leading to a cell collapse as observed in stippling areas in AA and PO. As shown in the present study, palisade parenchyma is usually the most affected tissue by O 3 (Günthardt-Goerg and Vollenweider, 2007;Paoletti et al, 2009). Our observations suggest that reactive oxygen species (ROS) degrades the pectins of the middle lamella inducing a separation of the mesophyll cells, and increasing intercellular spaces.…”
Section: Discussionsupporting
confidence: 77%
“…Maier-Maercker (1989) suggested that such slower stomatal response might be explained by delignification of the guard cell and subsidiary cells as recorded in ozonated Picea abies. No change in guard cell wall lignification, however, was observed in ozone-injured manna ash (Fraxinus ornus) leaves showing stomatal sluggishness (Paoletti et al, 2009). In manna ash, such slower stomatal responses were considered as accelerated senescence in the cell physiological processes (Paoletti et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…No change in guard cell wall lignification, however, was observed in ozone-injured manna ash (Fraxinus ornus) leaves showing stomatal sluggishness (Paoletti et al, 2009). In manna ash, such slower stomatal responses were considered as accelerated senescence in the cell physiological processes (Paoletti et al, 2009). Mills et al (2009) found that O 3 reduced stomatal sensitivity to ABA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…photosynthesis (Bagard et al, 2008;Feng et al, 2011;Schaub et al, 2005;Wittig et al, 2009;Zhang et al, 2010). The reduction in photosynthesis rate by O 3 could be attributed to stomatal closure, decreased chlorophyll content and electron transport rate, impaired carboxylation capacity and Rubisco content (Paoletti et al, 2009;Reich, 1983). Although the reduction in Rubisco activity was assumed to be the primary cause in photosynthetic decline under O 3 stress, stoma appeared to an important factor controlling O 3 entering the leaf interior (Novak et al, 2005).…”
Section: Introductionmentioning
confidence: 99%